2019
DOI: 10.3389/feart.2019.00211
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variability of Forces Controlling Sedimentation in the Sundarbans National Forest, Bangladesh

Abstract: Southwest Bangladesh, located on the Ganges-Brahmaputra-Meghna delta, is experiencing the impacts of sea level rise (SLR) due to processes at both the local and global scale. In particular, regional alterations of the hydrodynamic network, due to embankment construction, have drastically altered effective SLR, placing millions of inhabitants at risk of prolonged inundation, and threatening the world's largest continuous mangrove stand, the Sundarbans National Forest (SNF). In order to effectively employ landsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“…[57,70]). Both of the tidal point bars investigated in this study (DAC and BTG) are situated adjacent to major tidal channel confluences ( Figure 1B), which may generate irregular hydrodynamic conditions (e.g., eddying and rapid flow reversals [71]) and stratal architecture.…”
Section: Down-core Trends In Grain Sizementioning
confidence: 99%
“…[57,70]). Both of the tidal point bars investigated in this study (DAC and BTG) are situated adjacent to major tidal channel confluences ( Figure 1B), which may generate irregular hydrodynamic conditions (e.g., eddying and rapid flow reversals [71]) and stratal architecture.…”
Section: Down-core Trends In Grain Sizementioning
confidence: 99%
“…The six sites in the Ganges tidal floodplain chosen for this study span a wide range of surface water salinity and irrigation practices (Patton, 2018). The sites were located near Polder 32 and the Sundarbans, an area that has been the focus of numerous complementary field studies (Auerbach et al, 2015;Ayers et al, 2016Ayers et al, , 2017Benneyworth et al, 2016;Hale et al, 2019;Peters & Hornberger, 2019). Five sites were primarily used for agriculture, while one located in the Sundarbans mangrove forest represents natural background (Table 1 and Figure 1).…”
Section: Sampling Sitesmentioning
confidence: 99%
“…In more recent times, the forest has largely remained intact, exhibiting 1.2% net land loss between 1973 and 2000 [44], and <2% infilled tidal channels since the 1960s [45]. The stability of the SMF can be attributed to preservation measures establishing the forest as a reserve in 1875 (e.g., [43]), as well as the efficient dispersal of fluvial-and marine-sourced sediments by tides throughout the mangrove islands [25,37].…”
Section: Study Areamentioning
confidence: 99%
“…For instance, [24] found that mangrove mortality associated with the landfall of Hurricane Mitch caused widespread root decomposition and peat collapse, ultimately resulting in increased shallow subsidence and losses in surface elevation as much as 1.1 cm yr −1 . Even subtle changes in surface elevation can dramatically change the frequency, duration, and depth of inundation by tidal waters [25,26], which can lead to intolerable levels of root submergence and tree death [6].…”
Section: Introductionmentioning
confidence: 99%